IMPLEMENTASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN PADA MADRASAH BERBASIS PESANTREN: STUDI KASUS DI MADRASAH ALIYAH BAITUL ARQOM AL ISLAMI BANDUNG - Ahmad Khori; Lia Amalia; Muhamad Endang Szafei (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital technology has significantly transformed educational practices worldwide, including within Islamic educational institutions. The integration of digital technology into learning processes has become an essential strategy for improving educational quality, increasing learning effectiveness, and preparing students to meet the challenges of the twenty-first century. This study aims to analyze the implementation of digital technology in learning activities at Madrasah Aliyah Baitul Arqom Al Islami, a pesantren-based Islamic secondary school in Bandung, Indonesia. The research employed a qualitative approach using a case study design. Data were collected through classroom observations, semi-structured interviews, and documentation involving teachers and students. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that digital technology has been integrated into learning through the utilization of laptops, computers, projectors, internet-based resources, PowerPoint presentations, and educational videos. The implementation of digital technology has contributed positively to learning effectiveness by facilitating the delivery of instructional materials, increasing students’ learning motivation, expanding access to educational resources, and creating more interactive learning environments. However, the implementation process also faces several challenges, including limited technological facilities, unstable internet connectivity, and insufficient digital competence among some teachers. The study concludes that digital technology plays a strategic role in improving the quality of learning in Islamic educational institutions. Sustainable implementation requires adequate infrastructure, institutional commitment, and continuous professional development programs for teachers. The findings provide practical implications for strengthening digital transformation initiatives in madrasahs and other Islamic educational institutions.